Macroeconomic Indicators and Stock Market Boogie : The Case of National Stock Exchange, India - Das, Aniruddha; Megaravalli, Amith Vikram (Indian Journal of Research in Capital Markets, 2017)
The present paper intended to inspect the relationship between the selected macroeconomic variables and the Indian stock market by taking quarterly observations from April 2005 to March 2015. We considered exchange rate, foreign institutional investment, call money rate, and consumer price index (CPI) as macroeconomic variables. We applied Pearson's correlation, Augmented Dickey Fuller unit root test, Johansen co-integration test, and Granger causality test to check the relationship between stock market returns and the above mentioned variables. Our results discovered that positive correlation existed between macroeconomic variables and stock market indices and long run equilibrium existed with the NIFTY 50 Index. In addition, the Granger causality test revealed that causality ran from NIFTY 50 Index to exchange rate and call money rate to NIFTY 50 Index. Moreover, it was also observed that the stock indices' returns were not a leading indicator for macro economic variables.